Application of approaches to artificial intelligence and machine training in cyber security - Kadrev, Vasil; Pasarelski, Rosen (Yearbook Telecommunications, 2021)
Of interest is how machine learning is used in cybersecurity for both security and criminal activities, incl. and for cyberattacks targeting machine-learning models. The aim of the development is to show how machine learning, can be applied in the context of security in terms of both protection and attack, as well as the potential threats posed to machine learning models. Results were obtained using analytical descriptive methodology based on literature sources, examining the use of artificial intelligence techniques and machine learning to increase cybersecurity, as well as the most important areas of application that improve cybersecurity. On the other hand, the features and applications of artificial intelligence and machine learning in the service of cybercriminals are considered. Regarding the contribution part, an in-depth and extensive analysis of the features and applications of artificial intelligence and machine learning from two points of view (cybersecurity and cybercrime) has been made.